Analysis of the impact of macroprudential and microprudential policies on bank stability in Indonesia post-Covid-19 - Melati, Wanda Aprillia; Sitorus, Nurbetty Herlina; Maimunah, Emi; Emalia, Zulfa (Asian Journal of Economics and Business Management, 2025)
This research investigates the impact of macroprudential and microprudential policies on the stability of banks in Indonesia during the post-COVID-19 recovery period. The study applies an Error Correction Model (ECM) to panel data collected quarterly from the first quarter of 2020 to the fourth quarter of 2022, focusing on ten banks categorized as BUKU IV banks in Indonesia. The findings reveal that, in the long run, the macroprudential intermediation ratio significantly and positively influences the non-performing loan (NPL) ratio. Conversely, return on assets (ROA) and the loan-to-deposit ratio (LDR) exhibit a significant negative relationship with NPL. Meanwhile, the macroprudential liquidity buffer demonstrates a positive but statistically insignificant effect on NPL, whereas the capital adequacy ratio (CAR) shows a negative yet statistically insignificant relationship with NPL. In the short term, the results indicate that the macroprudential intermediation ratio retains its positive and significant influence on NPL. Similarly, ROA and CAR are found to have a significant negative impact on NPL, suggesting their importance in mitigating loan defaults. However, the macroprudential liquidity buffer continues to display a positive but statistically insignificant effect on NPL, while LDR demonstrates a negative but also statistically insignificant relationship with NPL. These findings underscore the complex dynamics between prudential policies and banking stability, emphasizing the varying impacts of key financial indicators over different time horizons.